Vasopressin casts light on the suprachiasmatic nucleus - Tsuji, Takahiro; Grinevich, Valéry (The journal of physiology, 2017)
Key points: A subpopulation of retinal ganglion cells expresses the neuropeptide vasopressin. These retinal ganglion cells project predominately to our biological clock, the suprachiasmatic nucleus (SCN). Light-induced vasopressin release enhances the responses of SCN neurons to light. It also enhances expression of genes involved in photo-entrainment of biological rhythms. Abstract: In all animals, the transition between night and day engages a host of physiological and behavioural rhythms. These rhythms depend not on the rods and cones of the retina, but on retinal ganglion cells (RGCs) that detect the ambient light level in the environment. These project to the suprachiasmatic nucleus (SCN) of the hypothalamus to entrain circadian rhythms that are generated within the SCN. The neuropeptide vasopressin has an important role in this entrainment. Many SCN neurons express vasopressin, and it has been assumed that the role of vasopressin in the SCN reflects the activity of these cells. Here we show that vasopressin is also expressed in many retinal cells that project to the SCN. Light-evoked vasopressin release contributes to the responses of SCN neurons to light, and enhances expression of the immediate early gene c-fos in the SCN, which is involved in photic entrainment of circadian rhythms.